Toll-Like Receptors Signaling Pathway of Quercetin Regulating Avian Beta-Defensin in the Ileum of Broilers - Ying, Linlin; Wu, Hao; Zhou, Shuaishuai; Lu, Han; Ding, Manyi; Wang, Bo; Wang, Shanshan; Mao, Yanjun; Xiao, Fenglin; Li, Yao (Frontiers in Cell and Developmental Biology, 2022)
The purpose of the experiment was to investigate the Toll-like receptor signaling pathway of quercetin regulating avian beta-defensin (AvBD) in the ileum of Arbor Acre (AA) broilers. Four hundred and eighty one-day-old Arbor Acre broilers with similar body weight, half male and female, were randomly allotted to four treatments; the control treatment and three dietary treatments were fed with the basal diets supplemented with 0, 0.02%, 0.04, and 0.06% quercetin, respectively. The results showed that dietary quercetin supplementation did not significantly influence growth performance (p > 0.05), but significantly decreased the mortality rate of broilers by 85.74%, 85.74, and 71.28%, respectively (p < 0.05, F = 9.06). Compared with control, dietary supplementation with 0.04 and 0.06% quercetin significantly upregulated mRNA expression of total AvBD (p < 0.05), and there were no significant differences in the mRNA expression of AvBD1, AvBD2, and AvBD14 in three quercetin supplementation groups in the ileum of AA broilers (p > 0.05). Dietary supplementation with 0.02 and 0.06% quercetin significantly downregulated the mRNA expression of total Toll-like receptors (p < 0.05). Dietary quercetin supplementation significantly downregulated the mRNA expression of TLR1A, TLR1B, and TLR2A (p < 0.05); however, there were no significant differences in the mRNA expression of TLR2B, TLR5, and TLR15 (p > 0.05). Dietary quercetin supplementation significantly downregulated the mRNA expression of myeloid differentiation primary response protein 88 (MyD88) and TIR domain-containing adaptor protein/MyD88-adaptor-like (TIRAP/MAL) (p < 0.05), 0.02% quercetin significantly downregulated the mRNA expression of tank-binding kinase1 (TBK1), IκB kinase complex-α (IKKα), IKKβ, IKKε, nuclear factor-kappa B (NF-κB), NF-κB inhibitor-alpha (IκBα), IκBα, IκBβ, TNF-receptor-associated factor 3 (TRAF3), and interferons regulatory factor 7 (IRF7) (p < 0.05), 0.04% quercetin significantly downregulated the mRNA expression of IKKβ, IKKε, NF-κB, IκBα, IκBβ, TRAF3, and TRAF6 (p < 0.05), and 0.06% quercetin significantly downregulated the mRNA expression of TBK1 and IKKα (p < 0.05). 0.02% quercetin significantly decreased the relative abundance of Escherichia, Staphylococcus (p < 0.05), and Salmonella (p < 0.01), 0.04% quercetin significantly decreased the relative abundance of Staphylococcus (p < 0.05), Escherichia, and Salmonella (p < 0.01), and 0.06% quercetin significantly decreased the relative abundance of Salmonella (p < 0.05) and Staphylococcus (p < 0.01) in the ileum of AA broilers. These findings suggested that dietary quercetin supplementation regulated the mRNA expression of AvBD, TLR, and the TLR signaling pathways and NF-κB signalling pathways, thereby maintaining the microecological balance of the intestinal tract and decreasing the mortality of broilers, and the optimum addition amount of quercetin is 0.04% under the test conditions.